Concurrent Computing in the Many-core Era (Dagstuhl Seminar 15021) - Philippsen, Michael; Felber, Pascal; Scott, Michael L.; Moss, J. Eliot B. (Schloss Dagstuhl–Leibniz-Zentrum fuer Informatik, 2015)
This report documents the program and the outcomes of Dagstuhl Seminar 15021 "Concurrent computing in the many-core era". This seminar is a successor to Dagstuhl Seminars 08241 "Transactional memory: From implementation to application" and 12161 "Abstractions for scalable multicore computing", respectively held in June 2008 and in April 2012. The current seminar built on the previous seminars by notably (1) broadening the scope to concurrency beyond transactional memory and shared-memory multicores abstractions, (2) focusing on the new challenges and potential uses of emerging hardware support for synchronization extensions, and (3) considering the increasing complexity resulting from the explosion in heterogeneity.
Keywords: Multi-/many-core processors; Concurrent Programming; Synchronization; Transactional Memory; Programming Languages; Compilation